The social and spatial manifestation of gated developments in the north-eastern suburbs of Cape Town - Welgemoed, Louis (Stellenbosch : Stellenbosch University, 2009)
Thesis (MA (Geography and Environmental Studies))--Stellenbosch University, 2009.